Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979426
|View full text |Cite
|
Sign up to set email alerts
|

Detecting vibrations across the body in mobile contexts

Abstract: In this paper we explore the potential and limitations of vibrotactile displays in practical wearable applications, by comparing users' detection rate and response time to stimuli applied across the body in varied conditions. We examined which body locations are more sensitive to vibrations and more affected by movement; whether visual workload, expectation of location, or gender impact performance; and if users have subjective preferences to any of these conditions. In two experiments we compared these factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 19 publications
6
67
2
3
Order By: Relevance
“…MuSS-bits by contrast emphasises flexibility in choice of body locations for its wireless sensor-display pairs. Choice of body location for haptics can have a variety of subtle effects on the perception of haptic signals beyond the scope of this chapter-a general discussion of this issue can be found in [49].…”
Section: Related Workmentioning
confidence: 99%
“…MuSS-bits by contrast emphasises flexibility in choice of body locations for its wireless sensor-display pairs. Choice of body location for haptics can have a variety of subtle effects on the perception of haptic signals beyond the scope of this chapter-a general discussion of this issue can be found in [49].…”
Section: Related Workmentioning
confidence: 99%
“…Placement location, number and types of tactors, arrangement, frequency, spacing, tempo, sequencing, connection methods and duration are all important factors when designing a wearable vibrotactile 'outfit' [9,10]. Karuei et al identified the wrists and spine as consistently most sensitive sites and found movement to be an impacting factor in decreasing detection rate [10] where Morrison et al found doing other activities reduced detection performance of vibrotactile stimuli [11].…”
Section: Related Backgroundmentioning
confidence: 99%
“…The wrist is one of the most sensitive body locations for vibrotactile stimuli, particularly during walking and standing when lower-limb sensitivity drops, and even with visuo-cognitive distractions [22,24]. A skin-exposed location where a presentation device could be worn, the wrist is also a key site for functional social touch as observed in human-to-human [21] and device-mediated [2] interaction.…”
Section: Tactile Perception: Body Locale and Iconographymentioning
confidence: 99%
“…Three synchronized eccentric-mass tactors (described in [22]). Multiple (more skin contact [35], redundancy), low cost tactors were spaced across the dorsal wrist at ~25mm intervals, parallel to the skin as in [6], and energized with pulsewidth modulated Arduino signals.…”
Section: System Componentsmentioning
confidence: 99%
See 1 more Smart Citation